Preparation method of super-hydrophilic photo-thermal carbon fiber cloth and water photovoltaic power generation sheet
By using ultra-hydrophilic photothermal carbon fiber cloth loaded with photothermal conversion particles in hydrovoltaic power generation equipment, the problems of limited operating time and low power generation efficiency of existing hydrovoltaic power generation equipment are solved, and efficient and continuous hydrovoltaic power generation is achieved.
Patent Information
- Application Number
- CN202411596673.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The operating time of existing hydrovoltaic power generation equipment is limited, the power generation efficiency and duration are limited, and the direction of movement of ions is consistent with the direction of water flow, limiting the power generation efficiency.
The ultra-hydrophilic photothermal carbon fiber cloth loaded with photothermal conversion particles is uniformly attached to the carbon fiber cloth through impregnation and brushing method, enhancing its photothermal interface evaporation ability, and modifying the surface by thermoplastic polyurethane solution. Hydrophilicity.
It has achieved improvement in the efficiency of photothermal conversion, extended the power generation time, improved the sustainability and efficiency of hydrovoltaic power generation, and the process is green and environmentally friendly and low-cost.
Smart Images

Figure CN119465657A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic, thermal and electric power cogeneration, and in particular to a preparation method of a super-hydrophilic photovoltaic carbon fiber cloth and a hydroelectric power generation sheet. Background Art
[0002] Seawater evaporation power generation technology mainly utilizes the wave energy and current energy of seawater, but has the disadvantages of high power generation cost and bulky power generation equipment, and is highly dependent on the seawater environment and geographical location, which limits its large-scale application. Therefore, developing an efficient, environmentally friendly and low-cost seawater evaporation power generation method is of great significance to solving global energy problems.
[0003] Solar-driven interfacial evaporation is a ubiquitous photothermal conversion process that has attracted extensive research attention due to its high conversion efficiency of solar energy and huge potential for industrial application. This method can reduce heat loss during evaporation and improve energy conversion efficiency [T. Peng, et al, Nature Energy, 2018, 3, 1031-1041]. It does not consume energy and has a relatively simple process. During the interfacial evaporation process, the photothermal conversion particles attached to the fiber matrix promote the supply of water flow, drive the movement of positive charges, form ion channels, and generate a potential difference between the two sections of the carbon fiber cloth, thereby achieving efficient evaporation-power generation and seawater desalination co-production. This method is called hydrovoltaic driven power generation. At present, hydrovoltaic power generation equipment mainly generates electricity through capillary penetration, which has the advantages of portability and easy operation; but when the water droplets completely wet the film, the capillary water flow stops, causing the ion movement to stop, and then the power generation process ends. The operating time of these devices is usually only tens of minutes, and the power generation time is limited. In addition, the movement direction of the ions is consistent with the direction of the water flow, which further limits the power generation efficiency and duration [H.Xia, et al, Nature Nanotechnology, 2024, 19, 1243-1244]; at this time, a suitable photothermal conversion coating is needed to promote evaporation, prevent the water droplets from completely wetting the film, ensure smooth ion channels, and continue the power generation process.
[0004] Photothermal conversion coatings are indispensable materials in interfacial solar evaporation technology, and their light absorption capacity and stability directly determine the efficiency of photothermal conversion. The photothermal conversion system composed of metal-based semiconductor nanoparticles in the present invention has the advantages of excellent absorption characteristics in the full spectrum range, diversified types, low cost, and easy functional application, and also has adjustable morphology and good photothermal stability. Therefore, photothermal conversion particles composed of carbon nanotubes, cesium tungsten bronze and copper sulfide are used, and they are loaded on carbon fiber cloth to form a photothermal conversion-hydrovoltaic power generation composite system. Based on this, the preparation of a super-hydrophilic photothermal carbon fiber cloth and its photothermal, water and electricity cogeneration application have important and wide application value. Summary of the invention
[0005] The purpose of the present invention is to provide a green, efficient and low-cost hydrovoltaic power generation method for the field of solar evaporation power generation, and thus a preparation method of a super-hydrophilic photothermal carbon fiber cloth and a hydrovoltaic power generation sheet are proposed. The photothermal carbon fiber cloth loaded with photothermal conversion particles in the present invention can absorb a large amount of solar energy and convert it into thermal energy.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a super-hydrophilic photothermal carbon fiber cloth comprises the following steps: dispersing photothermal conversion particles into a sodium dodecylbenzenesulfonate solution, performing ultrasonic dispersion treatment, and then mixing evenly with magnetic stirring to obtain a photothermal conversion coating; immersing the carbon fiber cloth into the photothermal conversion coating, then taking out the carbon fiber cloth, and using vacuum drying to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth; then applying a thermoplastic polyurethane solution on the surface of the photothermal carbon fiber cloth, and drying to obtain the photothermal carbon fiber cloth with super-hydrophilic properties.
[0008] Preferably, carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain the photothermal conversion particles. 0.32 WO 3 The molar ratio of carbon nanotubes and Cs 0.32 WO 3 / Cu 2 The mass ratio of S powder is 0.5~1:1~2.
[0009] Preferably, the mass fraction of sodium dodecylbenzenesulfonate solution is 0.5-2%, the ultrasonic time is 0.5-1h, and the magnetic stirring speed is 600-800r min -1 , the time is 1 to 2 hours. If the concentration of sodium dodecylbenzenesulfonate solution is too low or the magnetic stirring speed is too low or the time is too short, the mixed powder cannot be evenly dispersed in the system, and a certain amount of photothermal conversion particles cannot be formed; if the concentration of sodium dodecylbenzenesulfonate solution is too high or the magnetic stirring speed is too high or the time is too long, the photothermal conversion particles in the solution will agglomerate to form flocculation groups, the liquid fluidity will deteriorate, and the photothermal conversion efficiency and power generation will be reduced.
[0010] Preferably, the thickness of the carbon fiber cloth used is 1 to 4 mm, the number of immersions is 2 to 4 times, the immersion time for each time is 10 to 20 minutes, and the vacuum drying temperature is 50 to 60°C. If the carbon fiber cloth used is too thick, the positive charge movement rate will be slower and the power generation current will be lower; if the carbon fiber cloth used is too thin, the charge movement rate on the fiber matrix will be too fast, the ion channel will be blocked, and the power generation time will be limited. If the immersion time is too long or the number of immersions is too many, due to the limit on the amount of photothermal particles loaded on the carbon fiber cloth, some photothermal particles will not be attached to the fiber matrix and will be wasted; if the immersion time is too short or the number of immersions is too few, the fiber matrix will not be fully attached to the photothermal conversion particles, resulting in a decrease in the photothermal conversion efficiency.
[0011] Preferably, a thermoplastic polyurethane solution is applied to the surface of the photothermal carbon fiber cloth, followed by vacuum drying to obtain a super hydrophilic carbon fiber cloth. The number of times the thermoplastic polyurethane solution is applied is 2 to 4 times, and the vacuum drying temperature is 50 to 60°C. The number of times the coating affects the adhesion of the hydrophilic groups (hydroxyl groups) in the thermoplastic polyurethane solution to the carbon fiber cloth, and ultimately affects the hydrophilicity and photothermal conversion efficiency of the super hydrophilic carbon fiber cloth. If the number of coatings is too small, the hydrophilic groups in the thermoplastic polyurethane solution will be difficult to adhere to the surface of the carbon fiber cloth, and the insufficient hydrophilicity will cause the water flow to be unable to be supplied in time, and the hydrovoltaic power generation efficiency will be reduced; if the thermoplastic polyurethane solution is applied too many times, the surface coating of the super hydrophilic carbon fiber cloth will be thicker, the penetration of sunlight through the coating will be blocked, and the photothermal conversion particles will absorb limited photon energy, resulting in a decrease in the photothermal conversion efficiency. In addition, the photothermal conversion particles on the fiber matrix are firmly attached, resulting in a decrease in the flexibility of the super hydrophilic carbon fiber cloth, and the movement of ions in the fiber matrix is blocked, and the power generation current is reduced.
[0012] The present invention also provides a hydrovoltaic power generation sheet, which is formed by coating a thermoplastic polyurethane solution on a photothermal carbon fiber cloth loaded with photothermal conversion particles, and then tightly wrapping two ends of the cloth with thin copper sheets, which are welded with wires, thereby constructing the hydrovoltaic power generation sheet.
[0013] The present invention first prepares the photothermal carbon fiber cloth by an impregnation method, and then uses a brushing method to perform hydrophilic modification on the surface and interior of the photothermal carbon fiber cloth. 0.32 WO 3 / Cu 2 The S mixed powder is dispersed in a sodium dodecylbenzenesulfonate solution to form photothermal conversion particles, and the particles are attached to the carbon fiber cloth to enhance its photothermal interface evaporation ability; then a thermoplastic polyurethane solution is coated on the surface of the photothermal carbon fiber cloth to enhance the hydrophilic properties of the carbon fiber cloth, and finally a super-hydrophilic carbon fiber cloth with high photothermal conversion efficiency is obtained.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1) The selected sodium dodecylbenzenesulfonate solution has good dispersibility and can evenly disperse the photothermal conversion particles in the system without agglomeration. In the process of attaching the photothermal conversion particles to the carbon fiber cloth by the impregnation method, the loading amount of the photothermal particles and their dispersion degree can be effectively regulated by changing the impregnation time of the carbon fiber cloth and the concentration of the sodium dodecylbenzenesulfonate solution, thereby improving the photothermal conversion efficiency and preparing a photothermal carbon fiber cloth with rapid interface evaporation ability. The process is green, environmentally friendly, low-cost and easy to operate.
[0016] 2) By selecting carbon fiber cloth of appropriate thickness, the charge transfer rate in the fiber matrix can be controlled to achieve the optimal photothermal conversion efficiency and power generation.
[0017] 3) The brushing method uses thermoplastic polyurethane solution to increase the hydrophilicity of the carbon fiber cloth, enhance the capillary force and accelerate the water flow supply to drive hydrovoltaic power generation, while the water on the fiber matrix evaporates quickly to allow the power generation process to continue. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0019] Figure 1 Surface contact angle diagrams of the photothermal carbon fiber cloth in Example 1 (a) and Example 2 (b) of the present invention;
[0020] Figure 2 The sample temperature distribution diagram of the photothermal carbon fiber cloth in Example 1 (a) and Example 2 (b) of the present invention measured by an infrared temperature imaging camera under a simulated sunlight intensity;
[0021] Figure 3 This is a graph of the evaporation rate of the photothermal carbon fiber cloth in Example 1 and Example 2 of the present invention under a simulated sunlight intensity;
[0022] Figure 4 This is a diagram of power generation after the photothermal carbon fiber cloths prepared in Example 1 and Example 2 of the present invention are connected in series;
[0023] Figure 5 Surface contact angle diagrams of the photothermal carbon fiber cloth in Comparative Example 1(c) and Comparative Example 2(d) of the present invention;
[0024] Figure 6 The temperature distribution diagram of the samples of the photothermal carbon fiber cloth in Comparative Example 1 (a) and Comparative Example 2 (b) of the present invention measured by an infrared temperature imaging camera under a simulated sunlight intensity;
[0025] Figure 7 This is a graph of the evaporation rate of the photothermal carbon fiber cloth in Comparative Examples 1 and 2 of the present invention under a simulated solar light intensity. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0027] A method for preparing a super hydrophilic photothermal carbon fiber cloth, the steps are as follows:
[0028] Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain light-to-heat conversion particles, wherein Cs 0.32 WO 3 The molar ratio of carbon nanotubes and Cs 0.32 WO 3 / Cu 2 The mass ratio of S powder is 0.5-1:1-2. The photothermal conversion particles are dispersed in a sodium dodecylbenzene sulfonate solution, and then subjected to ultrasonic dispersion treatment and magnetic stirring to mix uniformly to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzene sulfonate solution is 0.5-2%, the ultrasonic time is 0.5-1h, and the magnetic stirring speed is 600-800r min -1 , the time is 1 to 2 hours. Soak the carbon fiber cloth in the photothermal conversion coating, then take out the carbon fiber cloth and vacuum dry it, so that the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 1 to 4 mm, the number of immersion times is 2 to 4 times, each immersion time is 10 to 20 minutes, and the vacuum drying temperature is 50 to 60°C. Finally, brush the thermoplastic polyurethane solution on the surface of the photothermal carbon fiber cloth, and then vacuum dry it to obtain a photothermal carbon fiber cloth with super hydrophilic properties. The number of times the thermoplastic polyurethane solution is brushed is 2 to 4 times, and the vacuum drying temperature is 50 to 60°C.
[0029] Example 1
[0030] This embodiment provides a method for preparing a super-hydrophilic photothermal carbon fiber cloth, comprising the following steps:
[0031] (1) Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain light-heat conversion particles, wherein Cs 0.32 WO 3 The molar ratio of carbon nanotubes and CuS is 1:1.0.32 WO 3 / Cu 2 The mass ratio of S powder is 1:1.
[0032] (2) The photothermal conversion particles are dispersed in a sodium dodecylbenzenesulfonate solution, and then dispersed by ultrasound, and then mixed evenly by magnetic stirring to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzenesulfonate solution is 2%, the ultrasonic time is 1 h, and the magnetic stirring speed is 800 r min -1 , time is 2h.
[0033] (3) The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 4 mm, the number of immersion times is 4 times, the immersion time each time is 20 minutes, and the vacuum drying temperature is 60°C.
[0034] (4) Finally, a thermoplastic polyurethane solution is applied on the surface of the photothermal carbon fiber cloth, followed by vacuum drying to obtain a photothermal carbon fiber cloth with hydrophilic properties. The thermoplastic polyurethane solution is applied four times, and the vacuum drying temperature is 60°C.
[0035] analyze Figure 1 (a) The surface contact angle test diagram shows that when the thermoplastic polyurethane solution is applied 4 times, the surface of the photothermal carbon fiber cloth is in a super-hydrophilic state, the contact angle is 0°, and the surface water film is thicker. Figure 2 As shown in (a), under the simulated sunlight intensity, the super-hydrophilic photothermal carbon fiber cloth was photographed by an infrared temperature imaging camera. The temperature rise of the super-hydrophilic photothermal carbon fiber cloth was not high within 15 minutes, and the temperature of the photothermal interface finally reached only 32.8°C. This is because the water film on the surface of the carbon fiber cloth is thick and the photothermal interface heats up slowly. The super-hydrophilic surface and high photothermal conversion performance are conducive to the carbon fiber cloth to absorb water from the bottom water body and transport it to the top by capillary force, and then the water on the top evaporates quickly (such as Figure 3 As shown in the figure, the evaporation capacity of a single piece of super hydrophilic photothermal carbon fiber cloth is as high as 1.79 kgm -2 h -1 ), indicating that the photothermal conversion particles are fully and evenly loaded on the carbon fiber cloth, making the material have better photothermal conversion performance.
[0036] Example 2
[0037] This embodiment provides a method for preparing a super hydrophilic carbon fiber cloth, comprising the following steps:
[0038] (1) Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain light-heat conversion particles, wherein Cs0.32 WO 3 The molar ratio of carbon nanotubes and CuS is 1:1. 0.32 WO 3 / Cu 2 The mass ratio of S powder is 1:1.
[0039] (2) Dispersing the photothermal conversion particles into a sodium dodecylbenzenesulfonate solution, dispersing the particles by ultrasonic treatment, and then mixing them uniformly by magnetic stirring to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzenesulfonate solution is 0.2%, the ultrasonic time is 30 min, and the magnetic stirring speed is 600 r min -1 , time is 1h.
[0040] (3) The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 1 mm, the number of immersions is 2, the immersion time each time is 10 min, and the vacuum drying temperature is 60°C.
[0041] (4) Then, a thermoplastic polyurethane solution is applied on the surface of the photothermal carbon fiber cloth, and then vacuum dried to obtain a photothermal carbon fiber cloth with hydrophilic properties. The number of times the thermoplastic polyurethane solution is applied is 2, and the vacuum drying temperature is 60°C.
[0042] (5) Finally, thin copper sheets are tightly wrapped around the two ends of the hydroelectric generator respectively. The thin copper sheets are welded with wires and any end is immersed in water as the bottom. The hydroelectric generator sheet is thus constructed. The carbon fiber cloth obtained in Example 1 is also used to construct a hydroelectric generator sheet. Subsequently, the two hydroelectric generator sheets are connected in series.
[0043] analyze Figure 1 (b) The surface contact angle test diagram shows that when the thermoplastic polyurethane solution is applied twice, the surface of the photothermal carbon fiber cloth is relatively hydrophilic, and the contact angle is 9.5°. Figure 2 As shown in (b), due to the thick water film on its surface, the infrared temperature camera captured that the photothermal carbon fiber cloth heated up rapidly within 15 minutes under the simulated sunlight intensity, and the final temperature of the photothermal interface reached 35.2℃. Figure 3 As shown in the figure, the evaporation capacity of a single piece of photothermal carbon fiber cloth is 1.64 kg m -2 h -1 Compared with Example 1, it is shown that the photothermal conversion particles are not fully loaded on the photothermal carbon fiber cloth, but a water flow can still be formed to drive the movement of ions to generate a potential difference. Figure 5 As shown in (c), after the photothermal carbon fiber cloths with hydrophilic properties prepared in Example 1 and Example 2 were connected in series, the voltage was stabilized at 2.2V, the output current was stabilized at 0.15mA, and the maximum power generation power was 0.43mW.
[0044] Example 3
[0045] This embodiment provides a method for preparing a super-hydrophilic photothermal carbon fiber cloth, comprising the following steps:
[0046] (1) Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain light-heat conversion particles, wherein Cs 0.32 WO 3 The molar ratio of carbon nanotubes and CuS is 2:0.5. 0.32 WO 3 / Cu 2 The mass ratio of S powder is 0.5:2.
[0047] (2) The photothermal conversion particles are dispersed in a sodium dodecylbenzene sulfonate solution, and then subjected to ultrasonic dispersion treatment and magnetic stirring to mix uniformly to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzene sulfonate solution is 0.5%, the ultrasonic time is 30 minutes, and the magnetic stirring speed is 800 r min -1 , time is 1h.
[0048] (3) The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 2 mm, the number of immersion times is 3 times, each immersion time is 20 min, and the vacuum drying temperature is 50°C.
[0049] (4) Finally, a thermoplastic polyurethane solution was applied on the surface of the photothermal carbon fiber cloth, followed by vacuum drying to obtain a photothermal carbon fiber cloth with hydrophilic properties. The thermoplastic polyurethane solution was applied three times, and the vacuum drying temperature was 50°C.
[0050] Example 4
[0051] This embodiment provides a method for preparing a super-hydrophilic photothermal carbon fiber cloth, comprising the following steps:
[0052] (1) Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain light-heat conversion particles, wherein Cs 0.32 WO 3 The molar ratio of carbon nanotubes and CuS is 2:1. 0.32 WO 3 / Cu 2 The mass ratio of S powder is 1:2.
[0053] (2) The photothermal conversion particles are dispersed in a sodium dodecylbenzene sulfonate solution, and then subjected to ultrasonic dispersion treatment and magnetic stirring to mix uniformly to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzene sulfonate solution is 1%, the ultrasonic time is 30 minutes, and the magnetic stirring speed is 800 r min -1 , time is 2h.
[0054] (3) The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 3 mm, the number of immersion times is 2, each immersion time is 10 min, and the vacuum drying temperature is 50°C.
[0055] (4) Finally, a thermoplastic polyurethane solution is applied on the surface of the photothermal carbon fiber cloth, followed by vacuum drying to obtain a photothermal carbon fiber cloth with hydrophilic properties. The thermoplastic polyurethane solution is applied twice, and the vacuum drying temperature is 50°C.
[0056] Comparative Example 1
[0057] (1) Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain photothermal conversion particles, Cs 0.32 WO 3 The molar ratio of carbon nanotubes and CuS is 1:1. 0.32 WO 3 / Cu 2 The mass ratio of S powder is 1:1.
[0058] (2) Dispersing the photothermal conversion particles into a sodium dodecylbenzenesulfonate solution, dispersing the particles by ultrasonic treatment, and then mixing them evenly by magnetic stirring to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzenesulfonate solution is 3%, the ultrasonic time is 1.5 h, and the magnetic stirring speed is 900 r min -1 , time is 2.5h.
[0059] (3) The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 5 mm, the number of immersion times is 5 times, the immersion time each time is 25 minutes, and the vacuum drying temperature is 60°C.
[0060] (4) Finally, a thermoplastic polyurethane solution was applied on the surface of the photothermal carbon fiber cloth, followed by vacuum drying to obtain a photothermal carbon fiber cloth with super hydrophilic properties. The thermoplastic polyurethane solution was applied five times, and the vacuum drying temperature was 60°C.
[0061] like Figure 5 As shown in (c), when the photothermal carbon fiber cloth is coated with thermoplastic polyurethane solution for 5 times, its surface is in a superhydrophilic state with a contact angle of 0°. Because the water film is thin, the temperature of the photothermal carbon fiber cloth interface rises to as low as 33.2°C after 15 minutes of simulated sunlight during the evaporation process recorded by the infrared temperature camera (as shown in Figure 2). Figure 6 (a)). Figure 7 As shown, the evaporation efficiency is as low as 1.31kgm -2 h -1 This is because the concentration of sodium dodecylbenzenesulfonate solution is too high, which causes the photothermal conversion particles to agglomerate, and the thermoplastic polyurethane solution is applied too many times, resulting in a thicker surface coating on the carbon fiber cloth, which hinders sunlight from penetrating the coating. The photothermal conversion particles absorb limited photon energy, and the photothermal conversion efficiency decreases.
[0062] Comparative Example 2
[0063] (1) Carbon nanotubes, cesium tungsten bronze and copper sulfide (Cs 0.32 WO 3 / Cu 2 S) powders are mixed together to obtain light-heat conversion particles, wherein Cs 0.32 WO 3 The molar ratio of carbon nanotubes and CuS is 1:1. 0.32 WO 3 / Cu 2 The mass ratio of S powder is 1:1.
[0064] (2) Dispersing the photothermal conversion particles into a sodium dodecylbenzenesulfonate solution, dispersing the particles by ultrasonic treatment, and then mixing them uniformly by magnetic stirring to obtain a photothermal conversion coating, wherein the mass fraction of the sodium dodecylbenzenesulfonate solution is 0.2%, the ultrasonic time is 20 min, and the magnetic stirring speed is 400 r min -1 , time is 0.5h.
[0065] (3) The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain the photothermal carbon fiber cloth. The thickness of the carbon fiber cloth used is 0.5 mm, the number of immersion times is 1, the immersion time is 5 min, and the vacuum drying temperature is 60°C.
[0066] (4) Finally, a thermoplastic polyurethane solution is applied on the surface of the photothermal carbon fiber cloth, followed by vacuum drying to obtain a photothermal carbon fiber cloth with hydrophilic properties. The thermoplastic polyurethane solution is applied once, and the vacuum drying temperature is 60°C.
[0067] analyze Figure 5(d) It can be seen that the number of times the thermoplastic polyurethane solution is applied is too small, the surface does not show a super-hydrophilic state, the contact angle is 16.2°, the surface does not reach a super-hydrophilic state and the water film is thin. The photothermal carbon fiber cloth heats up rapidly under simulated sunlight for 15 minutes, and the final temperature is as high as 37.2°C (such as Figure 6 (b) As shown in Figure 2, too high a surface temperature will cause a large loss in heat exchange between the evaporation interface and the environment, and most of the energy will not be utilized, and the photothermal evaporation efficiency will decrease accordingly. Figure 7 As shown, the photothermal evaporation rate is as low as 1.15 kg m -2 h -1 This is because the mass fraction of the sodium dodecylbenzenesulfonate solution is too low, so a large number of photothermal conversion particles cannot be formed. In addition, the carbon fiber cloth is immersed in the photothermal conversion coating for a small number of times and for a short time, resulting in the photothermal conversion particles not being completely attached to the carbon fiber cloth, the photothermal conversion efficiency is low, and the photothermal evaporation performance is poor.
Claims
1. A method for preparing a super hydrophilic photothermal carbon fiber cloth, characterized in that: The photothermal conversion particles are dispersed in a sodium dodecylbenzenesulfonate solution, and ultrasonic dispersion treatment is performed, followed by magnetic stirring to mix evenly to obtain a photothermal conversion coating. The carbon fiber cloth is immersed in the photothermal conversion coating, and then the carbon fiber cloth is taken out and vacuum dried to make the photothermal conversion particles adhere to the carbon fiber cloth to obtain a photothermal carbon fiber cloth. Subsequently, a thermoplastic polyurethane solution is applied on the surface of the photothermal carbon fiber cloth, and the cloth is dried to obtain a photothermal carbon fiber cloth with super hydrophilic properties.
2. The method for preparing a super hydrophilic photothermal carbon fiber cloth according to claim 1, characterized in that: Carbon nanotubes, cesium tungsten bronze and copper sulfide powder are mixed together to obtain photothermal conversion particles.
3. The method for preparing a super hydrophilic photothermal carbon fiber cloth according to claim 2, characterized in that: Cs 0.32 The molar ratio of WO3 and CuS is 1-2:0.5-1, and the molar ratio of carbon nanotubes and Cs 0.32 The mass ratio of WO3 / Cu2S powder is 0.5~1:1~2.
4. The method for preparing a super hydrophilic photothermal carbon fiber cloth according to claim 1, characterized in that: The mass fraction of sodium dodecylbenzenesulfonate solution is 0.5-2%, the ultrasonic time is 0.5-1h, and the magnetic stirring speed is 600-800r min -1 , time is 1 to 2 hours.
5. The method for preparing a super hydrophilic photothermal carbon fiber cloth according to claim 1, characterized in that: The thickness of the carbon fiber cloth used is 1-4 mm, the soaking times are 2-4 times, the soaking time each time is 10-20 minutes, and the vacuum drying temperature is 50-60°C.
6. The method for preparing a super-hydrophilic photothermal carbon fiber cloth according to claim 1, characterized in that: A thermoplastic polyurethane solution is coated on the surface of the photothermal carbon fiber cloth, which is then vacuum dried to obtain a photothermal carbon fiber cloth with super hydrophilic properties.
7. The method for preparing a super-hydrophilic photothermal carbon fiber cloth according to claim 6, characterized in that: The thermoplastic polyurethane solution is applied 2 to 4 times, and the vacuum drying temperature is 50 to 60°C.
8. A hydroelectric power generation sheet, characterized in that: The photothermal carbon fiber cloth with super hydrophilic properties obtained in claim 1 is tightly wrapped with thin copper sheets at both ends, and the thin copper sheets are welded with wires, thereby assembling a hydrovoltaic power generation sheet.
Citation Information
Patent Citations
Wettability regulation and control method of photo-thermal material and evaporator of photo-thermal material
CN118307841A
Cited By
Flexible Cu2O-Cu-C composite nanofiber membrane as well as preparation method and application thereof
CN120291282A